ANALISIS BIBLIOMETRIK TERHADAP TREND RISET “HALAL TOURISM” MENGGUNAKAN VOSVIEWER - Widiastiana Vista Wijaya; Citra Puspa Maulidina; Shilvy Andini Sunarto; Siti Zulzilah (Jurnal Sosial Humaniora dan Pendidikan, 2023)
The aim of bibliometric analysis is mapping research trends by processing metadata from Google Scholar. This research also wants to know the research trend on "Halal Tourism" which uses the Social Network Analysis method. Research through searching the Google Scholar database with the keywords "Halal Tourism". Retrieval of metadata using the Publish or Perish (POP) application. The resulting data from PoP is then analyzed descriptively based on the year the publication was published, publisher name, researcher productivity and journal ranking. To obtain an accurate research development map, PoP data was exported to Excel CSV file format and result as RIS, CSV data was made into a private table and RIS data was analyzed using the VOSviewer (VV) application. Article search results show that the number of research publications in 2013 - 2023 was 997 papers. This research is visualized into a network and explained into 3 visualizations, namely Network Visualization, Overlay Visualization, Density Visualization. The results of this visualization can be used as a reference or as important information for researchers to see research trends on "Halal Tourism" and opportunities related to this topic in the future.